A Critique Review of the book Fundamentals of Sports Marketing - Hamid Ghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study was to criticize the translation of book “Fundamentals of Sports Marketing” by Berenda G. Pitss and David Kent Stotler. This book was translated into Persian by Morteza Azimzadeh, Fateme Heidari and Abolghasem Bazmara and published by Ferdowsi University of Mashhad in 2017. A critical philosophical exploration was used to review this book. The criticism tool was a worksheet for reviewing textbooks in the Humanities Textbooks. Qualitative content analysis showed some findings. The book’s positive points included a form of cover design, typography, print quality, and proper bookbinding. These positive points of content dimension included the appropriateness of the content of the book with the objectives of the lesson in question and covering many of the chapters approved, matching the book with the scientific level of students, proper use of different scientific tools, and meeting the scientific and practical needs of the community.  The weak points included inconsistency in the text of some words, inconsistency in the translation, and inconsistency in the title with the cover image. Also, some concepts are not well explained, and detailed interpretations are not provided by the translator. Overall, the work under review is one of the best-translated books in the basics of sports marketing.